2023
DOI: 10.1186/s12903-023-02913-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dentin surface pretreatment using dimethyl sulfoxide on the bond strength of a universal bonding agent to dentin

Abstract: Background This study aimed to evaluate the effect of dentin pretreatment by Dimethyl Sulfoxide (DMSO) on the bond strength and microleakage of a universal bonding agent to dentin. Methods Fifty-six dentinal discs (thickness = 2 mm) were obtained from the crowns of the human third molars. The disks were assigned into 4 groups and treated as follows; self-etch-control group: G-Premio universal adhesive was used in self-etch mode, total-etch-control:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…On the other hand, 50% DMSO was found to significantly decrease the bond strength of a UA used by Mirzaei et al . ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 50% DMSO was found to significantly decrease the bond strength of a UA used by Mirzaei et al . ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 11 ) also reported that by disrupting the water layer bound to collagen molecules, DMSO promotes the exposure of more binding sites and allows more MDP molecules to bind with collagen. It also prevents collagen breakdown by blocking MMP-9 and MMP-2 enzymes ( 12 ). Different studies evaluated the effect of DMSO on immediate and long-term wet and dry dentin bond strength.…”
Section: Introductionmentioning
confidence: 99%